(untitled) (Tanzania Medical Journal, 2009)
Objective: To determine the prevalence of S. haematobiuminfection among schoolchildren in the three lowland divisions ofLushoto district. DESIGN: A cross sectional study.Setting: A rapid assessment of the presence of S. haematobiuminfection was conducted using a questionnaire survey amongschoolchildren in 20 primary schools in the three divisions.Subject: Nine thousand and thirty three hundred schoolchildrenaged between 6 and 15 years were examined for S. haematobiuminfection using a questionnaire which asked about past (1 month)and present experience of blood in urine.Results: The prevalence of reported blood in urine was calculated foreach division and Umba division recorded a significantly higherprevalence of 21.6% compared to Mlola and Mlalo divisions whichhad prevalence of 5.9 and 2.0%, respectively. Conclusion: Urinaryschistosomiasis is prevalent in Lushoto district particularly in Umbadivision.Keywords: Schistosoma haematobium, haematuria, questionnaire, prevalence, schoolchildren, Lushoto